The Study of the Progress of School Education In India.: A comprehensive analysis of school education in India and its challenges, achievements, and future prospects (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper provides an overview of school education in India.  Firstly, it places India s educationalachievements in international perspective, especially against countries withwhich it is now increasingly compared such as BRIC economies in general andChina in particular. India does well relative to Pakistan and Bangladesh butlags seriously behind China and the other BRIC countries, especially insecondary school participation and youth literacy rates.   Secondly, the paper examines schoolingaccess in terms of enrolment and school attendance rates, and schooling qualityin terms of literacy rates, learning achievement levels, school resources andteacher inputs.  The substantial silverlining in the cloud of Indian education is that its primary enrolment rates arenow close to universal. However, despite progress, attendance and retentionrates are not close to universal, secondary enrolment rates are low, learningachievement levels are seriously low and teacher absenteeism is high,signalling poor quality of schooling.  Thirdly, the paper examines the role of private schooling in India.While more modest in rural areas, the recent growth of private schooling inurban areas has been nothing short of massive, raising questions about growinginequality in educational opportunity. Evidence suggests that private schoolsare both more effective in imparting learning and do so at a fraction of theunit cost of government schools, their cost advantage being because they canpay market wages while government school teachers  bureaucratically setminimum wages have large rents in them which teacher unions have fought hard tosecure.  Lastly, the paper discusses somemajor public education initiatives such as Sarva Shiksha Abhiyan,mid-day meal and para-teacher schemes. The impacts of these massive interventions (and their sub-components) onchildren s schooling outcomes need to be rigorously evaluated to learnabout the cost-effectiveness of alternative interventions for better futurepolicy making. However, the existence of some of these initiatives and theintroduction of the 2% education cess to fund them suggests increased publiccommitment to school education and, together with increased NGO educationactivity, gives grounds for optimism about the future, even though manychallenges remain.